Killian-Jamieson Diverticulum Mimicking a Thyroid Tumor - Kazunori Kageyama; Yutaka Watanuki; Katsumi Endo; Makoto Daimon (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2015)
A 42-year-old woman was referred to us for evaluation of a suspicious mass in her left thyroid gland. She had experienced left anterior neck pain and odynophagia for a few weeks. Ultrasonography (US) demonstrated a heterogenous and hypoechoic mass with bright internal hyperechoic foci and a partial surrounding halo involving the posterior aspect of the left thyroid lobe (Figure 1). Computed tomography (CT) of the neck with contrast enhancement demonstrated a soft tissue mass with internal air between the left back side of the thyroid and esophagus (Figure 2). Barium swallow pharyngoesophagography showed a barium-filled sac protruding from the left anterolateral wall of the cervical esophagus (Figure 3).